Diagnóstico e quantificação de toxoplasma gondii através de PCR em tempo real em sangue periférico de recém-nascidos com toxoplasmose congênita no estado de Minas Gerais - Julia Gatti Ladeia Costa (2012)
Congenital toxoplasmosis has been associated with the occurrence of abortion, stillbirths and neonatal mortality. Infected newborns may have hydrocephalus, retinochoroiditis, cerebral calcifications and mental retardation or neurological disorders. Most infected children who are born asymptomatic, but without specific treatment, may develop late ocular lesions. Strategies for diagnosis (serological or parasitological) have limitations that difficult and/or delay the diagnosis of congenital toxoplasmosis that is essential for the early beginning of treatment and improvement in disease outcomes. This study aims to identify the presence of Toxoplasma gondii in DNA extracted from newborns peripheral blood. The qPCR technique, using a repetitive sequence of the parasite genome (rep529), was tested as an alternative tool for congenital toxoplasmosis fast diagnosis. Results of 183/220 (83,2%) samples was considered. Results of 37/220 (16,8%) were not available because they have PCR inhibitors or nonspecific products. In 84/183 (45.9%) samples the parasite presence was confirmed by amplification of the target rep529. The qPCR-rep529 has good reproducibility (82.86%). Twelve samples (6.5%) had positive molecular diagnosis despite absence of IgG after 12 months of life. There was no association between qPCR-rep529 and presence of cerebral calcifications, however, regarding the presence of ocular injury, the difference was significant (p = 0.013), with a relative risk (RR) of 1.8. Considering types of ocular lesion, it was demonstrated, that children with active retinochoroiditis have RR of 2.3 (p = 0.009) and those with healed retinochoroiditis have RR of 1.9 (p = 0.034). Quantification of peripheral blood parasites from infected newborns was done through qPCR-rep529. Children has small parasite load, 68% of positive samples has less than 0.5 tachyzoite parasites / ml of peripheral blood. The mean age of children were 58 months of life, however, time of life was not associated with parasite load. It was not possible to associate parasite load to the presence of cerebral calcifications or retinochoroiditis. There was intraspecific variation in the number of copies of the target rep529 when eight recombinant strains of T. gondii isolated from humans were analyzed.